1995
DOI: 10.1128/jcm.33.3.658-660.1995
|View full text |Cite
|
Sign up to set email alerts
|

Identification of varicella-zoster virus strains by PCR analysis of three repeat elements and a PstI-site-less region

Abstract: We established a method of identifying varicella-zoster virus (VZV) strains, especially those of the Oka vaccine, in patients with clinical VZV infections. The DNAs of 30 clinically isolated strains and 4 laboratory strains including the Oka vaccine strain and its parent VZV strain, were analyzed by PCR with four sets of primers for the four variable regions, R2, R4, R5, and a region without a PstI site (PS). R4 was unstable in four laboratory VZV strains and was excluded from the study. The other regions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 13 publications
0
21
1
Order By: Relevance
“…This is the first report of a PstI À BglI À VZV wild-type strain outside Australia and the first description of a PstI À wild-type strain in Germany. PstI À is a typical pattern of one-third of the Japanese wild-type strains and the Oka vaccine strain [Hondo et al, 1989;Takada et al, 1995], but all Japanese strains are BglI þ like the Oka vaccine strain [Takayama et al, 1996;Sauerbrei et al, 2003a]. Thus, our strain might result from recombination between dominant European strains and Oka vaccine strain or a European-type strain has acquired a PstI SNP by chance.…”
Section: Discussionmentioning
confidence: 98%
“…This is the first report of a PstI À BglI À VZV wild-type strain outside Australia and the first description of a PstI À wild-type strain in Germany. PstI À is a typical pattern of one-third of the Japanese wild-type strains and the Oka vaccine strain [Hondo et al, 1989;Takada et al, 1995], but all Japanese strains are BglI þ like the Oka vaccine strain [Takayama et al, 1996;Sauerbrei et al, 2003a]. Thus, our strain might result from recombination between dominant European strains and Oka vaccine strain or a European-type strain has acquired a PstI SNP by chance.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that absence of a Pst1 restriction site in ORF 38 and the presence of a Bgl1 restriction site in ORF 54 differentiate vOka from wild type US [LaRussa et al, 1992[LaRussa et al, , 1998] and European [Hawrami and Breuer, 1997;Sauerbrei et al, 2003] viruses. The differences reflect geographical variation between the Japanese vOka and non-Japanese strains, and these markers do not distinguish vOka from its parent wild type virus or from other wild type Japanese strains [Takada et al, 1995]. More recently, mutations in vOka which create Sma1 [Loparev et al, 2000], Nae1, and BssHII [Gomi et al, 2000] restriction enzyme cleavage sites in ORF 62 and a substitution in ORF 6, which abolishes an Alu1 site [Takayama and Takayama, 2004], have been described.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] In children acquiring herpes zoster subsequent to immunization, it is difficult to tell whether this results from vaccine-type or wild-type virus if the VZV is not differentiated. Several methods including restriction fragment length polymorphism (RFLP), 21 and PCR, 2,22 are available for differentiation of wild-type from vaccine-derived VZV strains. Lawrence et al 16 demonstrated five cases of zoster occurring among 346 children with acute lymphoblastic leukaemia who were immunized with live attenuated varicella vaccine.…”
Section: Discussionmentioning
confidence: 99%